Coral disease prevalence and compromised health in the Sempu Island Nature Reserve, Malang District, Indonesia - ANDIK ISDIANTO; ANGGER RIO FEWILA; SEFTIAWAN SAMSU RIJAL; ARIEF SETYANTO; AULIA LANUDIA FATHAH; DINI ATIKAWATI; BERLANIA MAHARDIKA PUTRI; INTAN DWI PUSPITASARI; OKTIYAS MUZAKY LUTHFI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Isdianto A, Fewila AR, Rijal SS, Setyanto A, Fathah AL, Atikawati D, Putri BM, Puspitasari ID, Luthfi OM. 2024. Coral disease prevalence and compromised health in the Sempu Island Nature Reserve, Malang District, Indonesia. Biodiversitas 25: 1404-1412. Since the Dutch colonialization era, the Malang District's Sempu Strait has been designated a natural reserve. Environmental changes and human activities have contributed to the 14.28% coral cover in the Sempu Strait. This study aims to assess coral health in the Sempu Strait and detect coral diseases or compromised conditions. At five stations, data were gathered utilizing the Underwater Photo Transect method with a 10-meter interval and a 1x1 meter transect implemented across 100 meters. The average coral cover in Sempu Strait is 14.28%, considered inadequate according to categories for determining coral reef status. Fish Bite, Black Band Disease (BBD), Ulcerative White Spots (UWS), Non-Focal Bleaching (NFBL), Trematodiasis, and Pigmentation Response are the six categories of coral reef diseases that have been identified. Sediment damage is the only compromised health condition that has been identified. With an average prevalence of 15.35%, Non-Focal Bleaching (NFBL) is the most prevalent disease; Black Band Disease (BBD) has the lowest prevalence at 0.8%. The insufficient coral coverage in the Strait of Sempu is caused by the surrounding environmental conditions that stress corals to the point where the prevalence of coral-eating diseases is increased.